Serum Nerve Growth Factor as a Biomarker for Chemotherapy-Induced Peripheral Neuropathy: A Cross-Sectional Study - Rifki Irsyad; Restu Susanti; Fanny Adhy Putri; Yuliarni Syafrita; Syarif Indra; Reno Bestari (HM Publisher, 2025)
Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a common and debilitating side effect of cancer treatment. Nerve growth factor (NGF) plays a crucial role in neuronal health and has been implicated in CIPN development. This study investigated the relationship between serum NGF levels and CIPN in cancer patients undergoing chemotherapy. Methods: A cross-sectional study was conducted on 60 cancer patients receiving chemotherapy at Dr. M. Djamil General Hospital Padang, Indonesia, from June to October 2024. Serum NGF levels were measured, and CIPN was assessed using the Toronto Clinical Scoring System (TCSS). The relationship between NGF and CIPN was analyzed using the Mann-Whitney test. Results: The median serum NGF level was significantly lower in patients with CIPN (n=43) compared to those without CIPN (n=17) (103.26 pg/ml vs. 148.91 pg/ml, p=0.029). No significant association was found between chemotherapy regimens and CIPN or NGF levels. Conclusion: Lower serum NGF levels are associated with CIPN in cancer patients undergoing chemotherapy. NGF may serve as a potential biomarker for CIPN, aiding in early detection and management. Further research is needed to explore the clinical utility of NGF as a predictive and monitoring tool for CIPN.